(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
This paper is devoted to seismic stability of subsiding undercompacted soils. Using grain-size limit curves after Tsushida and the coefficient of compaction of white soils it was established that saturated white soils with loamy and sandy composition lose their stability under seismic effects and liquеfaction takes place. For seismic zoning it’s proposed to take into account liquifaction factor of white soils.